2010
DOI: 10.1007/978-3-642-04088-7_4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Multiscale Methods for Flow Problems: Recent Developments

Abstract: The concept of the new fully adaptive flow solver Quadflow has been developed within the SFB 401 over the past 12 years. Its primary novelty lies in the integration of new and advanced mathematical tools in a unified environment. This means that the core ingredients of the finite volume solver, the grid adaptation and grid generation are adapted to each others needs rather than putting them together as independent black boxes. In this paper we shall present recent developments and demonstrate their efficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Multiwavelets (MW) are directly compatible with the piecewise-polynomial bases of FV and DG solvers and provide a multiresolution analysis that enables a dynamically adaptive solution that overcomes known shortcomings of conventional adaptive mesh refinement methods (Dahmen, 1997;Cohen et al, 2001;Müller, 2003;Lamby et al, 2005;Díaz Calle et al, 2005;Smith et al, 2008;Dahmen et al, 2010;Archibald et al, 2011;Hovhannisyan et al, 2013;Haleem et al, 2015;Kesserwani et al, 2015;Gerhard et al, 2015b;Gerhard and Müller, 2016;Guo and Cheng, 2016;Wang et al, 2016;Sharifian et al, 2019;Tao et al, 2019). Kesserwani et al (2019) adopted multiwavelets and Haar wavelets to formulate adaptive one-dimensional (1D) MWDG2 and HFV1 hydrodynamic solvers, and found that the 1D-MWDG2 solver achieved the accuracy of the uniform DG2 solver for a runtime cost less than the uniform FV1 solver.…”
Section: Introductionmentioning
confidence: 99%
“…Multiwavelets (MW) are directly compatible with the piecewise-polynomial bases of FV and DG solvers and provide a multiresolution analysis that enables a dynamically adaptive solution that overcomes known shortcomings of conventional adaptive mesh refinement methods (Dahmen, 1997;Cohen et al, 2001;Müller, 2003;Lamby et al, 2005;Díaz Calle et al, 2005;Smith et al, 2008;Dahmen et al, 2010;Archibald et al, 2011;Hovhannisyan et al, 2013;Haleem et al, 2015;Kesserwani et al, 2015;Gerhard et al, 2015b;Gerhard and Müller, 2016;Guo and Cheng, 2016;Wang et al, 2016;Sharifian et al, 2019;Tao et al, 2019). Kesserwani et al (2019) adopted multiwavelets and Haar wavelets to formulate adaptive one-dimensional (1D) MWDG2 and HFV1 hydrodynamic solvers, and found that the 1D-MWDG2 solver achieved the accuracy of the uniform DG2 solver for a runtime cost less than the uniform FV1 solver.…”
Section: Introductionmentioning
confidence: 99%
“…These provide advantages for various application cases, as detailed in a recent survey [BLP*13], where they are deemed ‘the most important class [of quad meshes] in terms of applications’. For instance, they enable the application of efficient adaptive and multi‐level solver schemes [BDL10, DHM09] in the context of quad‐based finite element simulation and the application of degree adaptation techniques in the context of isogeometric analysis [HCB05, Bom12]. Their high level of structuredness is of benefit for applications like mesh compression [AG05] and Fourier or wavelet‐based processing [AUGA08].…”
Section: Introductionmentioning
confidence: 99%